2007
DOI: 10.1172/jci30006
|View full text |Cite
|
Sign up to set email alerts
|

Role of a CUF1/CTR4 copper regulatory axis in the virulence of Cryptococcus neoformans

Abstract: The study of regulatory networks in human pathogens such as Cryptococcus neoformans provides insights into host-pathogen interactions that may allow for correlation of gene expression patterns with clinical outcomes. In the present study, deletion of the cryptococcal copper-dependent transcription factor 1 (Cuf1) led to defects in growth and virulence factor expression in low copper conditions. In mouse models, cuf1Δ strains exhibited reduced dissemination to the brain, but no change in lung growth, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
182
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(192 citation statements)
references
References 61 publications
8
182
1
1
Order By: Relevance
“…To survive, replicate and invade host tissues, pathogenic fungi have evolved efficient and sophisticated machineries to compete for essential nutrients, including metals. In the last decade, studies have implied that Cu is a key virulence modulator for C. neoformans and is required for fungal virulence 13,14,18,[26][27][28] . Fungal pathogens require Cu for maintaining normal cell growth and are equipped with Cu-detoxification defences, suggesting the possibility that fungal cells encounter both Cu scarcity and toxicity during their infectious life cycles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To survive, replicate and invade host tissues, pathogenic fungi have evolved efficient and sophisticated machineries to compete for essential nutrients, including metals. In the last decade, studies have implied that Cu is a key virulence modulator for C. neoformans and is required for fungal virulence 13,14,18,[26][27][28] . Fungal pathogens require Cu for maintaining normal cell growth and are equipped with Cu-detoxification defences, suggesting the possibility that fungal cells encounter both Cu scarcity and toxicity during their infectious life cycles.…”
Section: Discussionmentioning
confidence: 99%
“…29, revealed that a cuf1D strain is sensitive to both low and high Cu 12,29 . A subsequent study showed that Cuf1 controls the expression of the Cu transporter CTR4 and that the cuf1D strain is avirulent in a tail vein infection model, thus suggesting that Cu acquisition is essential for C. neoformans virulence in mice 18,27 . However, recent work has demonstrated that Cuf1 activates both the Cu-detoxification machinery and the Cu-acquisition machinery, in response to high or low Cu conditions, respectively 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the human pathogen Cryptococcus neoformans , MTs play a major role of in Cu detoxification [7]. Two MTs, Cmt1 and Cmt2, were shown to be important for fungal virulence in C. neoformans , both of which are regulated by the Cu-binding TF Cuf1 [2,18]. In Candida albicans , a membrane-localized P-type Cu ATPase, Crp1, is responsible for Cu resistance along with the MT Cup1, both of which are transcriptionally activated by Ace1 under high Cu conditions [1921].…”
Section: Introductionmentioning
confidence: 99%